Revision of the genus Pyrochlora Warren, 1895 (Lepidoptera: Geometridae: Geometrinae) - Viidalepp, Jaan (Zootaxa, 2009)
The genus Pyrochlora Warren is revised and three new species are described: P. motilonia, sp. nov. from Costa Rica and Nicaragua, P. kuklase, sp. nov. from mountainous Ecuador, and P. vogli, sp. nov. from Northern Venezuela. Wings pattern and genitalic structures of all five species are described and illustrated.